CAUSES OF PERIODONTITIS ORIGIN AND ITS COMPLICATIONS - Raxmonova Shoxsanom Raxim qizi, teacher (Western European Studies, 2024)
Periodontitis is a common dental disease that affects about 90% of the adult population of the planet. Just like caries, it leads to tooth loss. But if almost everyone knows about the dangers, causes and prevention of caries, then periodontitis is still a little-known disease for many.
Keywords: Teeth; periodontitis; healthy; medicine